Faktor- Faktor yang Mempengaruhi Motivasi Kinerja Karyawan dari Perspektif Etika Bisnis Islam - Astuti, Wiji Rahayu; Sisdianto, Ersi; Suprianingsih, Okta (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study examines the influence of psychological factors, such as job insecurity and job satisfaction, on the performance of contract employees at Indomaret in Bandar Lampung. Additionally, it analyzes these issues through the lens of Islamic business ethics, emphasizing principles such as justice, security, welfare, and social responsibility in workplace relationships. Research Methodology: A quantitative approach with a descriptive method was employed. The study population comprised contract employees at Indomaret outlets in Bandar Lampung, Indonesia. Data were collected via questionnaires distributed through purposive sampling and analyzed using SmartPLS to assess the direct effects of job insecurity and satisfaction on employee performance. Results: Job insecurity negatively and significantly affects employee performance, whereas job satisfaction has a positive and significant impact. From an Islamic ethical perspective, job insecurity is seen not only as an economic issue but also as a test of faith, while job satisfaction encompasses spiritual and moral values, as work is considered worship. Conclusion: The findings highlight the importance of addressing psychological factors in employee performance and integrating ethical principles into workplace management to foster fairness, productivity, and employee well-being. Limitations: This study is limited by its focus on a specific region and company, potentially reducing generalizability. Additionally, self-reported data may introduce a subjective bias. Contribution: This research integrates Islamic ethical values into human resource management, offering theoretical insights and practical recommendations for creating ethical, just, and productive work environments.